Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the problem, we need to use the Binomial Theorem to expand the expression [tex]\((4y + 2x)^3\)[/tex]. The Binomial Theorem states that:
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
For the expression [tex]\((4y + 2x)^3\)[/tex], we can identify:
- [tex]\(a = 4y\)[/tex]
- [tex]\(b = 2x\)[/tex]
- [tex]\(n = 3\)[/tex]
We will expand this expression by calculating each term where [tex]\(k\)[/tex] varies from 0 to [tex]\(n\)[/tex].
[tex]\[ (4y + 2x)^3 = \sum_{k=0}^{3} \binom{3}{k} (4y)^{3-k} (2x)^k \][/tex]
Let's compute each term individually:
### Term when [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{3}{0} (4y)^{3-0} (2x)^0 = \binom{3}{0} (4y)^3 = 1 \cdot 64y^3 = 64y^3 \][/tex]
### Term when [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{3}{1} (4y)^{3-1} (2x)^1 = \binom{3}{1} (4y)^2 (2x) = 3 \cdot 16y^2 \cdot 2x = 3 \cdot 32y^2x = 96y^2x \][/tex]
### Term when [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{3}{2} (4y)^{3-2} (2x)^2 = \binom{3}{2} (4y) (2x)^2 = 3 \cdot 4y \cdot 4x^2 = 3 \cdot 16yx^2 = 48yx^2 \][/tex]
### Term when [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{3}{3} (4y)^{3-3} (2x)^3 = \binom{3}{3} (4y)^0 (2x)^3 = 1 \cdot 8x^3 = 8x^3 \][/tex]
So the expansion of [tex]\((4y + 2x)^3\)[/tex] is:
[tex]\[ (4y + 2x)^3 = 64y^3 + 96y^2x + 48yx^2 + 8x^3 \][/tex]
To find the 4th term, we look at the sequence of terms obtained. The 4th term in this expansion is:
[tex]\[ 8x^3 \][/tex]
Hence, the 4th term is:
[tex]\[ 8x^3 \][/tex]
Thus, the correct answer among the given choices is:
[tex]\[ \boxed{8x^3} \][/tex]
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
For the expression [tex]\((4y + 2x)^3\)[/tex], we can identify:
- [tex]\(a = 4y\)[/tex]
- [tex]\(b = 2x\)[/tex]
- [tex]\(n = 3\)[/tex]
We will expand this expression by calculating each term where [tex]\(k\)[/tex] varies from 0 to [tex]\(n\)[/tex].
[tex]\[ (4y + 2x)^3 = \sum_{k=0}^{3} \binom{3}{k} (4y)^{3-k} (2x)^k \][/tex]
Let's compute each term individually:
### Term when [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{3}{0} (4y)^{3-0} (2x)^0 = \binom{3}{0} (4y)^3 = 1 \cdot 64y^3 = 64y^3 \][/tex]
### Term when [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{3}{1} (4y)^{3-1} (2x)^1 = \binom{3}{1} (4y)^2 (2x) = 3 \cdot 16y^2 \cdot 2x = 3 \cdot 32y^2x = 96y^2x \][/tex]
### Term when [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{3}{2} (4y)^{3-2} (2x)^2 = \binom{3}{2} (4y) (2x)^2 = 3 \cdot 4y \cdot 4x^2 = 3 \cdot 16yx^2 = 48yx^2 \][/tex]
### Term when [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{3}{3} (4y)^{3-3} (2x)^3 = \binom{3}{3} (4y)^0 (2x)^3 = 1 \cdot 8x^3 = 8x^3 \][/tex]
So the expansion of [tex]\((4y + 2x)^3\)[/tex] is:
[tex]\[ (4y + 2x)^3 = 64y^3 + 96y^2x + 48yx^2 + 8x^3 \][/tex]
To find the 4th term, we look at the sequence of terms obtained. The 4th term in this expansion is:
[tex]\[ 8x^3 \][/tex]
Hence, the 4th term is:
[tex]\[ 8x^3 \][/tex]
Thus, the correct answer among the given choices is:
[tex]\[ \boxed{8x^3} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.